HISTOPATOLOGI PANKREAS TIKUS (Rattus norvegicus) DIABETES MELITUS YANG DIBERI EKSTRAK ETANOL BAWANG BATAK (Allium chinense G.Don) - Tri Novitashari Butar-Butar; Husnarika Ferbriani; Rasyidah Rasyidah; Syukriah Syukriah (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2022)
Diabetes mellitus occurs due to insulin resistance and disruption of insulin secretion. Bawang Batak (Allium chinense G.Don) is a herbal plant that is often used by the community as a traditional medicine for the treatment of diabetes mellitus, but there have been no preclinical studies. This study aims to determine the effect of bawang batak extract on the histopathology of the pancreas of alloxan-induced diabetes mellitus rats. This study used rats as experimental animals which were divided into 6 groups (normal control, negative control, metformin group, P1:bawang batak extract dose 250 mg/kg, P2:500 mg/kg, and P3:750 mg/kg), with 4 repetitions. The histological preparations of pancreas were made using the paraffin method with hematoxylin-eosin staining. Data were analyzed using one-way ANOVA and Duncan's test. The statistical results showed that there was a significant difference (p <0.05) in the diameter and area of islet langerhans between the control group and the treatment group. The diameter and area of islet Langerhans improved when compared to the negative control group. It can be concluded that the onion extract has an effect on the improvement of pancreatic in rats with diabetes mellitus and the most effective dose of bawang batak extract is 500 mg/kg.